DEMOKRASI EKONOMI DAN KONTRIBUSI EKONOMI ISLAM DALAM UNDANG-UNDANG DASAR1945 - Ali Murtadho (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
Integration of Islamic teachings has given a significant contribution for Indonesian economic life and establishment of Indonesian basic constitution namely the Undang-Undang Dasar (UUD) 1945. The founding fathers of Indonesia has elaborated the substance of economic value in the 1945's by using “economic democracy” term. Descriptive-analytical method and historical literary approach were applied in this study to explore the economic democracy in relation with the teachings of Islamic economy in the UUD 1945, especially in the discussion on social welfare. The results of study found that the democratic system of Indonesian economy is a distinctive model of economy system, while it is different from capitalist and liberal economics. The democratic system of Indonesian economy, which refers to 1945, were implemented in the form of Koperasi as an economic system. Principlly it rejects to capitalism and liberalism, while integrating the Islamic economics values. At the same time, it combines with the Indonesian economic values called “populist economy’.